Correlation between SQUID and Fluxgate Magnetometer Data-sets for Geomagnetic Storms: Hermanus - Matladi, Thabang-Kingsley (Stellenbosch : Stellenbosch University, 2014)
Thesis (MEng)--Stellenbosch University, 2014.